2006
DOI: 10.1152/ajpregu.00752.2005
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract improves running endurance in mice by stimulating lipid utilization during exercise

Abstract: A series of polyphenols known as catechins are abundant in green tea, which is consumed mainly in Asian countries. The effects of catechin-rich green tea extract (GTE) on running endurance and energy metabolism during exercise in BALB/c mice were investigated. Mice were divided into four groups: nonexercise control, exercise control (Ex-cont), exercise+0.2% GTE, and exercise+0.5% GTE groups. Treadmill running time to exhaustion, plasma biochemical parameters, skeletal muscle glycogen content, beta-oxidation ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(173 citation statements)
references
References 29 publications
10
161
1
1
Order By: Relevance
“…The forced swimming model has been used to evaluate the anti-fatigue effects of various compounds, [12][13][14][15] since this apparatus works well for evaluating the endurance capacity of mice and gives a high reproducibility. 10) BE was found to prolong the swimming time in this forced swimming test, indicating that BE possesses an anti-fatigue effect (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forced swimming model has been used to evaluate the anti-fatigue effects of various compounds, [12][13][14][15] since this apparatus works well for evaluating the endurance capacity of mice and gives a high reproducibility. 10) BE was found to prolong the swimming time in this forced swimming test, indicating that BE possesses an anti-fatigue effect (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This apparatus was used to evaluate the endurance capacity of mice that had been administered with various compounds. [12][13][14][15] Male 5-week-old CD2F-1 mice were made to swim for 20 min at a flow rate of 6 l/min twice in one week to accustom them to swimming. We selected mice suitable for evaluating endurance capacity following the method described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Information about the ImageJ macro language is available at rsb.info.nih.gov/ij/developer/macro/macros. html [6][7][8][9][10] …”
Section: Quantification Of Hepatic Collagen Content Before and After mentioning
confidence: 99%
“…Murase et al [89] have shown in mice that 8 to 10 weeks ingestion of green tea extract, containing concentrated levels of various catechin molecules, increased endurance exercise performance when combined with exercise training. However, they did not report whether green tea extract alone enhanced endurance.…”
Section: Pgc-1αmentioning
confidence: 99%
“…Green tea catechins can activate AMPK in non-muscle cells [90,91], suggesting a mechanism similar to other AMPK activators such as AICAR [55] and resveratrol [50]. However, Murase et al [89] suggest that the actions of green tea extract in skeletal muscle are independent of PPARα/δ signalling, which contrasts with the purported mechanism of AICAR treatment [55]. Green tea extract/catechin ingestion could therefore be part of a potential exercise mimetic strategy; however, more work is required to determine the signalling mechanisms responsible, as well as whether green tea extract/catechin can act alone or only in concert with training.…”
Section: Pgc-1αmentioning
confidence: 99%